A Monte Carlo model of an agility head for a 10-MV photon beam. Issue 1 (31st December 2022) - Almatani, Turki; Hugtenburg, Richard P.; Smakovs, Artjoms
Abstract : Objective: Modelling linear accelerator (linac) photon beams using the Monte Carlo (MC) technique is presently the most precise technique with which to calculate radiotherapy beam data. Complicated treatment plans can be achieved by using the Agility multileaf collimator. The focus of this study is to model a linac, integrated with an Agility head, using EGSnrc MC code and to investigate its accuracy compared with actual measurements. Methodology: A 10-MV photon beam from an Agility head installed in an Elekta Synergy linac was simulated using BEAMnrc MC code. Various incident electron energies were used to generate percentage depth dose curves for the MC model and were compared with measurements using gamma analysis ( γ ). Consequently, the focal spot with different full width half-maximums (FWHMs) was used to tune dose profiles. In addition, any differences in dose profiles were further minimized using different angular divergences. Results: The electron energy of 9.6 MeV was found to represent the best match with the measurements, where the γ pass rate was 100%. For dose profile comparisons, a circular focal spot with an FWHM of 0.45 cm and an angular divergence of 0.04 ∘ produced the best match with the measurements. Conclusion: The presented MC linac model integrated with an Agility head for a 10-MV photon beam can be reliably used for dose calculations.